IgG subclasses in smokers with chronic bronchitis and recurrent exacerbations - Qvarfordt, I; Riise, G C; Andersson, B A; Larsson, S (Thorax, 2001)
BACKGROUND Tobacco smokers have lower serum levels of IgG than non-smokers. IgG subclass deficiency is common in patients with recurrent respiratory infections. Recurrent bronchial infections are common in smokers with chronic bronchitis (CB). We have investigated whether susceptibility to recurrent exacerbations in smokers with CB is associated with altered IgG subclass levels or IgG subclass deficiency. METHODS Serum levels of IgG, IgA, IgM, and IgG subclasses 1–4 were determined by radial immunodiffusion in 100 subjects: 33 smokers with stable CB and recurrent exacerbations, 24 asymptomatic smokers, and 43 healthy never smokers. Systemic tobacco exposure was verified and excluded using a serum cotinine ELISA. Immunoglobulin data were log transformed to enable use of parametric statistical methods. RESULTS Compared with never smokers, both patients with CB and asymptomatic smokers had significantly lower levels of IgG (median 9.7 g/l (range 5.6–15.2) and 9.9 (6.1–12.1) g/l v 12.0 (6.9–18.5) g/l) and IgG2 (2.8 (0.9–5.9) g/l and 2.5 (1.0–6.3) g/lv 4.0 (1.7–10.2) g/l). The estimated ratio of median values between the patients with CB and never smokers was 0.78 (95% confidence interval (CI) 0.69 to 0.89) for IgG and 0.65 (95% CI 0.50 to 0.83) for IgG2. The corresponding ratios between asymptomatic smokers and never smokers were 0.79 (95% CI 0.69 to 0.91) and 0.60 (95% CI 0.50 to 0.83), respectively. There were no significant differences between the smoking groups. CONCLUSIONS Susceptibility to recurrent exacerbations in smokers with CB is not associated with lower levels of IgG subclasses than can be accounted for by smoking per se.